Advanced high strength steel (AHSS) development through chemical patterning of austenite. (15th March 2018) - Sun, W.W.; Wu, Y.X.; Yang, S.C.; Hutchinson, C.R.
Abstract: A new approach for the development of medium Mn AHSS is proposed in this work. It exploits a fine scale ( 100 nm) chemical patterning of Mn in austenite that may be obtained by the austenitisation of a pearlite structure formed under conditions with strong Mn partitioning between ferrite and cementite. The resulting 'ghost pearlite' ferrite/austenite can be subsequently treated to exhibit an interesting combination of ultimate tensile strength (UTS) (1600–2100 MPa) and ductility (7–10% elongation). The simple steel composition and very short processing provides a UTS-ductility combination similar to maraging steels and super bainitic steels. Graphical abstract: Image 1